2019
DOI: 10.1101/19003558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phenome-wide analysis of short- and long-run disease incidence following Recurrent Pregnancy Loss using data from a 39-year period

Abstract: Background: Pregnancy loss is one of the most frequent pregnancy complications. It is unclear how recurrent pregnancy loss (RPL) impacts disease risk later in life and if later disease risk is different in women with or without a live birth prior to RPL (primary vs. secondary RPL). We sought to investigate if women have an increased risk of disease following RPL, and if there was a difference between primary and secondary RPL. Methods: Using population-wide health care registry databases from Denmark we identi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Our conclusion that consecutive pregnancy losses have a larger impact than the total number of pregnancy losses is consistent with a recent publication from our group where consecutive pregnancy losses had a much larger effect on chance of live birth in the next pregnancy than the total number of pregnancy losses experienced 27 . The observation that women with three or more consecutive pregnancy losses have a reduced completed family size adds to the growing evidence that there are maternal and/or pathophysiological causes underlying the condition that put these women at risk beyond random chance, also of risk of disease later in life 6,10,13,14,16 . We believe that the clear results of our study were possible because of the very large sample sizes we could work with, but independent replication studies of consecutive pregnancy losses in other populations are clearly needed.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our conclusion that consecutive pregnancy losses have a larger impact than the total number of pregnancy losses is consistent with a recent publication from our group where consecutive pregnancy losses had a much larger effect on chance of live birth in the next pregnancy than the total number of pregnancy losses experienced 27 . The observation that women with three or more consecutive pregnancy losses have a reduced completed family size adds to the growing evidence that there are maternal and/or pathophysiological causes underlying the condition that put these women at risk beyond random chance, also of risk of disease later in life 6,10,13,14,16 . We believe that the clear results of our study were possible because of the very large sample sizes we could work with, but independent replication studies of consecutive pregnancy losses in other populations are clearly needed.…”
Section: Discussionsupporting
confidence: 91%
“…However, we did not specifically study trends of selective fertility in the present cohort and therefore we do not know if the decrease in number of live‐born children is due to infertility, continued adverse pregnancy outcomes, or if couples stop trying. Lastly, our study represents a population average, but individual disease trajectories, social circumstances, and lifestyle will explain a considerable proportion of individual‐level variance that we could not capture 10,28,29 . Specifically, smoking and body mass index were not registered before 1991 and 2003, respectively, and are only registered in pregnancies ending in a birth, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational methods provide the opportunity to mine this data and uncover patterns within patient populations. Previous projects analyzing EHR data to study RPL have investigated disease incidence after RPL 36 and characterized lifetime phenotypic associations of idiopathic RPL 15 . The first study included 10,691 RPL patients from Denmark, and reported an increased risk of cardiovascular and gastrointestinal disorders later in life, for primary and secondary RPL patients respectively 36 .…”
Section: Introductionmentioning
confidence: 99%